Pengembangan Pendidikan Agama Islam Berbasis Budaya - Artha Darwis; Khairunnisa; Asnani. M. Saula; Fakhira (Program Pascasarjana IIQ Jakarta, 2025)
The development of Islamic Religious Education (PAI) based on culture is an effort to integrate religious values ​​into the context of local culture in society. This approach aims to strengthen religious understanding by considering local wisdom in everyday life. Islamic Religious Education based on culture views the importance of understanding religion not only through teaching texts, but also through traditions and customs that already exist in society. This allows for synergy between religious and cultural values, which can ultimately form a balanced character and personality. In this context, culture plays a role as a means to convey religious teachings in a way that is more easily accepted by society. For example, existing cultural rituals can be combined with Islamic teachings, so that people can feel the closeness between their religious and cultural lives. The development of culture-based PAI can also strengthen religious identity in the context of cultural pluralism in Indonesia. In addition, the development of culture-based PAI provides an opportunity to develop learning methods that are more contextual and relevant to the social conditions of society. By utilizing the potential of local culture, religious teaching can be more interesting, effective, and well-received by various levels of society, without eliminating the essence of the religious teachings themselves. Keywords: Islamic Religious Education (PAI), Local Culture, Integration of Religion and Culture, Local Wisdom, Learning Development.